Nilai Gizi Otak-Otak Ikan Berbahan Dasar Surimi Ikan Bandeng (Chanos chanos) dengan Berbagai Penambahan Bahan Pengisi - Nurlaeli Fattah; Muh. Kasim; Ikbal Syukroni; Rahmaniar Rahmaniar (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aimed to evaluate the nutritional value of fish brain-brain products using milkfish surimi (Chanos chanos.Forskal) as the base ingredient, with variations in fillers such as tapioca flour, egg white, and Eucheuma cottonii seaweed. Three formulations were used: (F1) surimi + tapioca starch, (F2) surimi + egg white, and (F3) surimi + Euchema cottonii seaweed. Proximate analyses were conducted to determine the moisture, protein, fat, ash, and carbohydrate content. The results showed that the addition of various fillers had a significant effect (P>0.05) on the value of protein, carbohydrate and water in the brain. While for fat and ash content, there was no significant effect (P<0.05). The average water content ranged from 66.5% to 72%, with the lowest content in the brain-brain added with tapioca flour. The highest protein content was obtained in the P2 treatment (egg white), which was 18.9%, while the treatment with the addition of tapioca flour showed the lowest protein content of 12.8%. Sensory value using Kruskal waliss treatment that gets a high average value is the aroma, taste, and texture of the addition of egg white fillers, while the texture is with the addition of Euschema cottonii seaweed fillers. Egg white significantly increased the protein content. The best formulation based on nutritional content and panellists' liking value was F2 (Surimi + Egg white). This study shows the potential for the development of milkfish-based processed products that are highly nutritious and functional..